Albania and the Admission of the People's Republic of China to the OUN. Albanian Proposal to the UN in 1963 - Nita, Etleva (Richtmann Publishing, 2012)
In the framework of International Relations of the Cold War, after the break with the Soviet Union in 1961, the direction of theAlbanian foreign policy entered in a new stage, making a very pragmatic choice toward remote Communist China. The generous help ofthe PRC, by loans or grants, was a very suitable solution to survive for Peoples Republic of Albania. This help was paid back with theinvolvement and commitment of the Albanian diplomacy as a representative for the PRC in OUN. The Albanian diplomacy during 1960-1970, a period of a very good cooperation with China, was fully concentrated to a single goal–The admission of Peoples Republic ofChina in OUN. The debate on re-establishment of the legal rights of PRC on OUN, according to Albanian diplomacy, was itself a harshaccuse for the US policy against China. This diplomatic activity of the Albanian mission, leaded by official Tirana, coordinated withBeijing, started its activity with the proposal of 1963 to set in the daily agenda the issue of PRC admission in OUN, presented in the XVIIIsession of the General Assembly of OUN. But how would this proposal be expected and in what extend would it be influent in theAlbanian diplomatic mission up to 1971!